Current-mode PID controllers employing commercially available active components - Yurdem, Betul; Sagbas, Mehmet; Ayten, Umut E. (ELSEVIER GMBH, 2024)
This work describes two current -mode (CM) PID controllers using only two commercially active components, namely, current feedback operational amplifier (CFOA), and four passive components, i.e. two capacitors and two resistors. They have appropriate output and input impedance values, allowing them to be utilized in cascade connections without requiring a buffer circuit. Since all capacitors are grounded, it is suitable for integrated circuit (IC) technology. Moreover, the controllers can be easily modified to operate in voltage -mode (VM), transimpedance-mode (TIM), and transadmittance-mode (TAM) PID controllers. Using 0.18 mu m CMOS parameters and the PSPICE program, the proposed circuits are simulated to verify the theoretical behavior. To demonstrate the viability of the circuits, experimental tests using commercially available AD844 integrated circuits are performed. The suggested PID circuits are also experimental tested in a closed -loop system as an example.
Keywords: Current-mode circuits; Analog circuits; PID controllers; Current feedback operational amplifier; AD844; DESIGN; Engineering; Telecommunications